Ponatinib with fludarabine, cytarabine, idarubicin, and granulocyte colony-stimulating factor chemotherapy for patients with blast-phase chronic myeloid leukaemia (MATCHPOINT): a single-arm, multicentre, phase 1/2 trial. Issue 2 (February 2022) - Copland, Mhairi; Slade, Daniel; McIlroy, Graham; Horne, Gillian; Byrne, Jenny L; Rothwell, Kate; Brock, Kristian; De Lavallade, Hugues; Craddock, Charles; Clark, Richard E; Smith, Matthew L; Fletcher, Rachel; et al.
Summary: Background: Outcomes for patients with blast-phase chronic myeloid leukaemia are poor. Long-term survival depends on reaching a second chronic phase, followed by allogeneic haematopoietic stem-cell transplantation (HSCT). We investigated whether the novel combination of the tyrosine-kinase inhibitor ponatinib with fludarabine, cytarabine, granulocyte colony-stimulating factor, and idarubicin (FLAG-IDA) could improve response and optimise allogeneic HSCT outcomes in patients with blast-phase chronic myeloid leukaemia. The aim was to identify a dose of ponatinib, which combined with FLAG-IDA, showed clinically meaningful activity and tolerability. Methods: MATCHPOINT was a seamless, phase 1/2, multicentre trial done in eight UK Trials Acceleration Programme-funded centres. Eligible participants were adults (aged ≥16 years) with Philadelphia chromosome-positive or BCR-ABL1 -positive blast-phase chronic myeloid leukaemia, suitable for intensive chemotherapy. Participants received up to two cycles of ponatinib with FLAG-IDA. Experimental doses of oral ponatinib (given from day 1 to day 28 of FLAG-IDA) were between 15 mg alternate days and 45 mg once daily and the starting dose was 30 mg once daily. Intravenous fludarabine (30 mg/m 2 for 5 days), cytarabine (2 g/m 2 for 5 days), and idarubicin (8 mg/m 2 for 3 days), and subcutaneous granulocyte colony-stimulating factor (if used), were delivered according to local protocols. We used an innovative EffTox design to investigate the activity and tolerability of ponatinib–FLAG-IDA; the primary endpoints were the optimal ponatinib dose meeting prespecified thresholds of activity (inducement of second chronic phase defined as either haematological or minor cytogenetic response) and tolerability (dose-limiting toxicties). Analyses were planned on an intention-to-treat basis. MATCHPOINT was registered as an International Standard Randomised Controlled Trial, ISRCTN98986889, and has completed recruitment; the final results are presented. Findings: Between March 19, 2015, and April 26, 2018, 17 patients (12 men, five women) were recruited, 16 of whom were evaluable for the coprimary outcomes. Median follow-up was 41 months (IQR 36–48). The EffTox model simultaneously considered clinical responses and dose-limiting toxicities, and determined the optimal ponatinib dose as 30 mg daily, combined with FLAG-IDA. 11 (69%) of 16 patients were in the second chronic phase after one cycle of treatment. Four (25%) patients had a dose-limiting toxicity (comprising cardiomyopathy and grade 4 increased alanine aminotransferase, cerebral venous sinus thrombosis, grade 3 increased amylase, and grade 4 increased alanine aminotransferase), fulfilling the criteria for clinically relevant activity and toxicity. 12 (71%) of 17 patients proceeded to allogeneic HSCT. The most common grade 3–4 non-haematological adverse events were lung infection (n=4 [24%]), fever (n=3 [18%]), and hypocalcaemia (n=3 [18%]). There were 12 serious adverse events in 11 (65%) patients. Three (18%) patients died due to treatment-related events (due to cardiomyopathy, pulmonary haemorrhage, and bone marrow aplasia). Interpretation: Ponatinib–FLAG-IDA can induce second chronic phase in patients with blast-phase chronic myeloid leukaemia, representing an active salvage therapy to bridge to allogeneic HSCT. The number of treatment-related deaths is not in excess of what would be expected in this very high-risk group of patients receiving intensive chemotherapy. The efficient EffTox method is a model for investigating novel therapies in ultra-orphan cancers. Funding: Blood Cancer UK and Incyte.